PENGARUH PERILAKU KEPEMIMPINAN CAMAT TERHADAP MOTIVASI KERJA PEGAWAI DI KECAMATAN CEPOGO KABUPATEN BOYOLALI - Ambyah Atas Aji (Universitas Slamet Riyadi, 2017)
This study aims to gain an understanding of the influence of leadership behavior camat on the motivation of employees working in the district of Boyolali Cepogo and determine the influence of leadership behavior camat on the motivation of employees working in the District Cepogo Boyolali. The results of the analysis describes the motivation of employees working in the District Cepogo where the motive factors (impulse) is the highest of 105,7 aspect, this suggests that in increasing the motivation of employees working in each run the tasks assigned by management to provide the best possible service to community. Application of leadership behaviors camat oriented tasks, relationships, and changes that take place at the District Office Cepogo has been quite good, but not optimal. There is a strong influence and significant correlation between leadership behaviors camat on the motivation of employees working at the district office Cepogo District which is indicated by the value of the correlation coefficient of R = 0,858 and the coefficient of determination (R Square) which showed that motivation of employees affected by the behavior of the leadership of camat by 73,7% and the remaining 26,3% were caused by other factors not examined.Keywords: leadership, work motivation